2014
DOI: 10.1590/s0034-8910.2014048005286
|View full text |Cite
|
Sign up to set email alerts
|

Legal and health variations in drug litigation injunctions granted in Minas Gerais

Abstract: OBJECTIVE To investigate the factors related to the granting of preliminary court orders [injunctions] in drug litigations.METHODS A retrospective descriptive study of drug lawsuits in the State of Minas Gerais, Southeastern Brazil, was conducted from October 1999 to 2009. The database consists of 6,112 lawsuits, out of which 6,044 had motions for injunctions and 5,167 included the requisition of drugs. Those with more than one beneficiary were excluded, which totaled 5,072 examined suits. The variables for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
6
0
4
Order By: Relevance
“…The above testimony ratifies experts' position, who affirm that judicialization is a strategy the citizens adopt to safeguard their rights, initially employed individually, and more recently in the collective dimension ( 11 ) . The prevalence of individual over collective rights stands out when observing that collective were replaced by individual historical forms of struggle, through the use of the legal route, in which the Judiciary Power is acknowledged as an ally of citizenship ( 12 ) . Nevertheless, the prevalence of merely legal and not political language can harm the group, management and the implementation of policies at the different health levels and contexts ( 1 , 12 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The above testimony ratifies experts' position, who affirm that judicialization is a strategy the citizens adopt to safeguard their rights, initially employed individually, and more recently in the collective dimension ( 11 ) . The prevalence of individual over collective rights stands out when observing that collective were replaced by individual historical forms of struggle, through the use of the legal route, in which the Judiciary Power is acknowledged as an ally of citizenship ( 12 ) . Nevertheless, the prevalence of merely legal and not political language can harm the group, management and the implementation of policies at the different health levels and contexts ( 1 , 12 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The articles of Marques and Dallari 57 and Vieira 98 can be considered milestones in that field. Subsequently, several articles on legal demands for medications in many States of Brazil 22 , 53 , 90 were published. The relations between the productive sector of medications with high technological incorporation and the legal system were unveiled by Chieffi and Barata 20 , which identified that a small number of lawyers answered by most of the lawsuits filed against SUS.…”
Section: Resultsmentioning
confidence: 99%
“…8 Tal fato é destacado pelo exemplo exposto no estudo de Silva et al (2017), 9 em que a incorporação da alfaglicosidase ao SUS em 2014 gerou queda nos gastos com a judicialização deste: de R$ 2.153.732,50 em 2015 para R$ 637.198,97 de janeiro a agosto de 2016. Dada a importância disso, oito estudos 9,10,14,15,23,24,25,28 discorreram sobre os custos de medicamentos e seu impacto financeiro, além de 12 publicações 3,8,9,10,16,19,21,[23][24][25][26][27] dissertarem sobre a demanda de medicamentos.…”
Section: Discussionunclassified
“…Neste raciocínio e considerando a totalidade de concessão de liminares por parte dos juízes neste estudo e a necessidade em alguns casos de comprovação clínica patológica, 21 uma vez que tais não apresentam formação acadêmica médica, acabam por designar um médico perito para avaliar indicação da prescrição ou avaliam os argumentos daquele que assiste o demandante, sempre tomando por base documentos médicos e não jurídicos. 16 Os magistrados têm de julgar um parecer médico sem apresentar profundo conhecimento sobre tais causas 16 o que pode influenciar no julgamento.…”
Section: Discussionunclassified
See 1 more Smart Citation